Relações entre o uso do solo e supracomunidades endoparasitárias no nordeste brasileiro - Carvalho, Elvis Franklin Fernandes de (2024)
Parasitism plays a key role in ecosystems, representing a crucial way of life for trophic networks functioning. In this context, a comprehensive study of this ecological relationship is necessary, given the inherent complexity of this way of life and its interactions with other associated organisms. Hence, human activities, particularly agriculture, emerge as potential threats to the environment, with possible impacts on several ways of life, including parasitism. Given this consideration, this thesis aims to investigate how human agricultural practices may affect parasitism. To address this question, we propose using lizard endoparasites as study models. Endoparasites are intriguing study models due to their location within host populations, allowing investigations at various organization levels, with specialized terminology that integrates aspects of ecology and parasitology. Lizards are considered study models for hosts due to their multifaceted roles in the food web, acting as both predators and prey. Additionally, the population abundance and varied lifestyles of these animals make them viable options for investigations in different ecosystem environments. Data collection for this research was conducted in three conservation units and their surroundings, located in the Northeast region of Brazil. Specifically, the Aiuaba Ecological Station and Ubajara National Park, both located in the state of Ceará, and the Sete Cidades National Park, located in the state of Piauí. The results presented in this thesis highlight the impacts of agriculture on parasite communities, demonstrating population declines in cases of heteroxenous life cycles. Furthermore, encompass the richness of parasitic species associated with lizards in the collection areas, followed by identified parasitological predictors. Additionally, new records of parasitic infections related to the studied species are presented. The structure of this thesis is divided into four sections: 1) General introduction, presenting the theoretical framework and justification for the study of parasitism in the face of anthropogenic disturbances, including general definitions related to parasitism, with a focus on reptiles, and the reasons for the choices of models and study areas; 2) Description of the richness of parasitic species associated with hosts in the study areas, including new records of infections and a discussion of the importance of faunal surveys for parasites, especially in preserved areas; 3) Analysis of the influence of agriculture on parasitic communities; 4) Synthesis and conclusion, proposing a reflection on the main results obtained, the development of the work, and prospects for future research